Activity of Ancillary Heterotrophic Community Members in Anaerobic Methane-Oxidizing Cultures - Zhu, Qing-Zeng; Wegener, Gunter; Hinrichs, Kai-Uwe; Elvert, Marcus (Frontiers in Microbiology, 2022)
Consortia of anaerobic methanotrophic archaea (ANME) and sulfate-reducing bacteria mediate the anaerobic oxidation of methane (AOM) in marine sediments. However, even sediment-free cultures contain substantial numbers of additional microorganisms not directly related to AOM. To track the heterotrophic activity of these community members and their possible relationship with AOM, we amended meso- (37 ℃) and thermophilic (50 ℃) AOM cultures (dominated by ANME-1 archaea and their partner bacteria of the Seep-SRB2 clade or Candidatus Desulfofervidus auxilii) with L leucine-3-13C (13C-leu). Various microbial lipids incorporated the labeled carbon from this amino acid, independent of the presence of methane as an energy source, specifically bacterial fatty acids such as iso and anteiso-branched C15:0 and C17:0 as well as unsaturated C18:1ω9 and C18:1ω7. In natural methane-rich environments, these bacterial fatty acids are strongly 13C-depleted and thus, we suggest that those fatty acids are produced by ancillary bacteria that grow on 13C-depleted necromass or cell exudates/lysates of the AOM core communities. Candidates that likely benefit from AOM biomass are heterotrophic bacterial members of the Spirochaetes and Anaerolineae, known to produce abundant branched fatty acids and present in all the AOM enrichment cultures. Analysis of intact polar archaeol-derived phytane showed only little 13C incorporation, yet still suggested 13C leu anabolism. Based on their relatively high abundance in the culture, the most probable archaeal candidates are Bathyarchaeota, Thermoplasmatales, and Lokiarchaeota. All bacterial and archaeal ancillary members are likely key players in driving organic carbon recycling in anoxic marine sediments.